2019
DOI: 10.1051/0004-6361/201833374
|View full text |Cite
|
Sign up to set email alerts
|

Gaia Data Release 2

Abstract: Context. The Gaia second Data Release (DR2) presents a first mapping of full-sky RR Lyrae stars and Cepheids observed by the spacecraft during the initial 22 months of science operations. Aims. The Specific Objects Study (SOS) pipeline, developed to validate and fully characterise Cepheids and RR Lyrae stars (SOS Cep&RRL) observed by Gaia, has been presented in the documentation and papers accompanying the Gaia first Data Release. Here we describe how the SOS pipeline was modified to allow for processing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
283
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(290 citation statements)
references
References 67 publications
5
283
0
1
Order By: Relevance
“…The brightest extratidal star (G = 15.8 mag) shares the same region as the locus of intratidal HB stars. In fact, both Abbas et al (2014) and Clementini et al (2019) list this star as being a pulsating RR Lyrae star of type ab. The former authors provide a distance estimate of 10.99 kpc, whichlacking a proper attached error margin on that value -is hard to compare with the cluster distance of 10.2 kpc, although an association seems feasible.…”
Section: (Ngc 5272)mentioning
confidence: 95%
See 2 more Smart Citations
“…The brightest extratidal star (G = 15.8 mag) shares the same region as the locus of intratidal HB stars. In fact, both Abbas et al (2014) and Clementini et al (2019) list this star as being a pulsating RR Lyrae star of type ab. The former authors provide a distance estimate of 10.99 kpc, whichlacking a proper attached error margin on that value -is hard to compare with the cluster distance of 10.2 kpc, although an association seems feasible.…”
Section: (Ngc 5272)mentioning
confidence: 95%
“…A few hundred stars in our analysis fall inside the fundamental mode RR Lyraes' instability strip boundaries provided by Clementini et al (2019), intrinsically making them candidates for possible variability. In order to investigate their periodic alternation, we retrieved their photometry from the time domain Catalina sky survey (CSS, Drake et al 2009).…”
Section: Appendix A: Rr Lyrae Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…In the near future, we plan to enlarge our sample by including data from additional spectroscopic surveys, e.g., the GALAH survey (De Silva et al 2015), as well as additional photometrically identified RRLs from the recent time-domain surveys, e.g. the Pan-STARRS1 (Chamber et al 2016;Sesar et al 2017); the Gaia DR2 (Clementini et al 2019). We expect to have precise measurements of metallicities, systemic radial velocities and distances of RRLs for the whole sky.…”
Section: Comparison With Gaia Parallaxesmentioning
confidence: 99%
“…In this context, the Gaia mission (Gaia Collaboration et al 2016) is producing a 3D-map of 1 billion stars of the Milky Way with unprecedented accuracy. Focusing on pulsating stars, after the recent Data Release 2 (Gaia Collaboration et al 2018;Holl et al 2018), a large sample of Cepheids, observed in three photometric bands (G, G BP and G RP ) complemented with accurate parallaxes and proper motions, is available to the scientific community (Clementini et al 2019;Ripepi et al 2019), and the future releases will provide also radial velocity time series. This important database represents a challenging benchmark for testing the physical and numerical assumptions of current pulsation models.…”
Section: Introductionmentioning
confidence: 99%